The Canadian Senate in Bicameral Perspective. - Smith, David E. (University of Toronto Press, 2003)
The Canadian Senate in Bicameral Perspective sets the Canadian Senate into this international milieu, contextualizing the debate and arguing for a renewed investigation into its future.